Pediatric Toxidrome Simulation Curriculum: Liquid Nicotine Overdose - Arvin Radfar Akhavan; Rebekah Burns; Kimberly Stone; Jennifer Reid; Suzan Mazor (Association of American Medical Colleges, 2018)
Introduction Liquid nicotine exposure is becoming more common in the pediatric population. Toxicity may occur with exposure to small quantities given the high concentrations in solutions available commercially. Effects can include altered mental status, seizure, and death. Methods This simulation-based case involves the identification and management of a toddler presenting with acute liquid nicotine exposure, with emphasis on the general approach to the acutely ill pediatric patient, consideration in toxic exposures, and the presentation of nicotine exposure. Providers should assess airway, breathing, and circulation while concurrently providing supportive care for an actively seizing simulated patient, necessitating appropriate selection of medications and acute airway management. Additionally, providers must maintain a broad differential diagnosis and obtain a focused history to narrow that differential and identify toxic exposure as a cause of the patient's presentation. Preparatory and didactic material is provided to help the instructor prepare the simulation environment, guide learners through the case, and debrief with learners afterward. Results We implemented this curriculum with four pediatric emergency medicine fellows and 15 pediatric residents during two sessions. Feedback was overwhelmingly positive; participants who completed evaluations reported high levels of confidence with knowledge and skills directly related to the educational objectives after participation (mean Likert scores of 4.9 out of 5 in response to effectiveness of the case in teaching evaluation and management of nicotine toxicity). Discussion This comprehensive resource will aid in offering continuing education for providers and specifically in educating learners with regard to acute liquid nicotine exposure in a child.